Effectiveness of nitrogen and bio-fertilizer choice for improving growth and yield of hybrid rice (Oryza sativa L.) during dry season - Pal, Sukanta; Sana, Megha; Banerjee, Hirak; Lhungdim, Lhingneikim (ORYZA-An International Journal of Rice, 2021)
Effect of nitrogen and bio-fertilizer on growth and productivity of hybrid rice (cv. PHB 71) was assessed during dry seasons of 2017 and 2018 at Research Farm of BCKV under new alluvial zone of West Bengal. The experiment was laid out in factorial randomized block design with 12 treatment combinations having 4 levels of N and 3 types of bio-fertilizer replicated thrice. Application at 180 kg N/ha produced tallest plants at 90 DAT with maximum LAI (60 DAT), DMA (90 DAT), tillers/hill (90 DAT) and CGR (30-60 & 60-90 DAT). The same N rateresulted in highest panicles/m2, panicle length, panicle weight, filled grains/panicle and 1000-grain weight. A decrease in N dose from 180 to 150 kg/ha caused reduction in all those yield components; however, the variation was non-significant except for number of panicles/m2. Maximum grain yield, straw yield and harvest index was also achieved with 180 kg N/ha accounting 120.1, 34.9 and 32.8% more than the values obtained with zero-N; however, it was statistically at par with the yields and HI obtained with 150 kg N/ha. The Azospirillum application increased all the growth parameters, yield components and yield of hybrid rice over other tested bio-fertilizers (Azospirillum > PSB > K mobilizer), accounting 5.9 and 8.8% more than the yields obtained withPSB and K mobilizer. The interaction of N and bio-fertilizer exerted significant effect on growth attributes but failed to record any significant variations in yield components and yield of hybrid rice. The maximum economic benefit was achieved with combined application of 180 kg N/ha and Azospirillum.